Catalytic co-pyrolysis of rubber waste and polyacrylonitrile for producing BTEX enriched oil via heterogeneous Diels-Alder reaction. (1st August 2022) - Pan, Yuhan; Song, Jiaxing; Lou, Fangfang; Xu, Jun; Zhou, Yonggang; Huang, Qunxing
Graphical abstract: Highlights: Heterogeneous Diels-Alder reaction was applied for producing BTEX enriched oil. Quantitative analysis of the BTEX products was conducted. Diels-Alder reaction was significantly promoted by Zn loaded HZSM-5 zeolite. A highest BTEX yield of 22.01 wt% was obtained. Rubber wastes have potential to be an alternative fuel for producing valuable BTEX. Abstract: Monocyclic aromatic hydrocarbons are important chemicals with huge market demands. Recycling valuable hydrocarbons such as BTEX from rubber wastes is a sustainable and promising way, which can reduce the dependence on petroleum. Catalytic co-pyrolysis of rubber waste and polyacrylonitrile were conducted in this study, aiming to produce BTEX enriched light oil by enhancing the Diels-Alder reaction. The effects of catalytic mode, catalyst type, and mass ratio of the feedstocks were investigated to optimize the catalytic conditions for increasing BTEX yield. Meanwhile, quantitative analysis was performed with regard to BTEX by external standard methods. It was found that the primary pyrolytic products of rubber waste and polyacrylonitrile were rich in isoprene and dienophiles, respectively, which suggested it was feasible to enhance Diels-Alder reaction through the strategy of catalytic co-pyrolysis of rubber waste and polyacrylonitrile. The optimal result was obtained under the condition of ex-situ catalysis, Zn/HZSM-5 as catalyst, and Rubber-to-PAN ratio of 1:3, at which case the BTEX yield reached 22.01 wt%, much higher than those in previous literatures. This work provides a new strategy for recovering high value-added products (BTEX) from rubber wastes, which has the potential to be an alternative fuel in the future.